CFAP54 is required for proper ciliary motility and assembly of the central pair apparatus in mice - McKenzie, Casey W. (Mol Biol Cell, 2015)
Motile cilia and flagella play critical roles in fluid clearance and cell motility, and dysfunction commonly results in the pediatric syndrome primary ciliary dyskinesia (PCD). CFAP221, also known as PCDP1, is required for ciliary and flagellar function in mice and Chlamydomonas reinhardtii, where it localizes to the C1d projection of the central microtubule apparatus and functions in a complex that regulates flagellar motility in a calcium-dependent manner. We demonstrate that the genes encoding the mouse homologues of the other C. reinhardtii C1d complex members are primarily expressed in motile ciliated tissues, suggesting a conserved function in mammalian motile cilia. The requirement for one of these C1d complex members, CFAP54, was identified in a mouse line with a gene-trapped allele. Homozygous mice have PCD characterized by hydrocephalus, male infertility, and mucus accumulation. The infertility results from defects in spermatogenesis. Motile cilia have a structural defect in the C1d projection, indicating that the C1d assembly mechanism requires CFAP54. This structural defect results in decreased ciliary beat frequency and perturbed cilia-driven flow. This study identifies a critical role for CFAP54 in proper assembly and function of mammalian cilia and flagella and establishes the gene-trapped allele as a new model of PCD.